Synthesis of Ag/CeO2 Nanocomposites with Noni Leaf Extract and Its Potential Antibacterial Properties - Laellia Denada; Poedji Loekitowati Hariani; Nabila Aprianti (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
This study aims to perform green synthesis of Ag/CeO2 nanocomposites using noni leaf extract and to test their potential antibacterial activity. The synthesis results were characterised using X-ray Diffraction (XRD) to determine crystallite size, Scanning Electron Microscope-Energy Dispersive Spectroscopy (SEM-EDX) to observe morphology and elemental composition, and Fourier Transform Infrared Spectroscopy (FTIR) to identify functional groups. The XRD characterization results showed the formation of typical Ag/CeO2 peaks with an average crystallite size of 15,28 nm. SEM analysis revealed morphology in the form of aggregates with varying sizes. EDX results confirmed the presence of Ag, Ce, and O elements. FTIR analysis showed the presence of typical Ce–O group absorption bands, which supports the successful synthesis of Ag/CeO2. The synthesized nanocomposites were then tested for their antibacterial activity against Escherichia coli and Staphylococcus aureus bacteria. Antibacterial activity tests showed the formation of an 8 mm zone of inhibition (ZOI) at a concentration of 5000 ppm, demonstrating the potential of the synthesized green Ag/CeO2 as an antibacterial agent. This study confirms that the use of noni leaf extract as a reducing and stabilizing agent is an environmentally friendly approach and has potential for environmental applications.